Rehabilitacija bolnikov s pljučnim rakom - Sakelšek-Jeras, Ljudmila (Rehabilitacija (Ljubljana), 2008)
Rehabilitation of patients with lung cancer aims to improve their quality of life by means of controlling and alleviating the symptoms and effects of the disease and its treatment. The main requirement is a patient's motivation created by a motivated health-care team. The main causes of the decreased quality of life in patients with lung cancer include pain, decreased lung capacity with dyspnea, fear and anxiety as well as decreased physical abilities. All these can be influenced on by a well-planned multidisciplinary program of treatment and rehabilitation. The plan requires good evaluation of a patient's capacity of respiratory, cardio-vascular and locomotor systems, the evaluation of outcome and adjusting to the patient. The article outlines the guidelines for organizing, planning and managing rehabilitation.
Keywords: fizioterapija; pljučni rak